Human genes involved in copy number variation: mechanisms of origin, functional effects and implications for disease - de Smith, A.J. (S. Karger AG, 2009)
Copy number variants (CNVs) overlap over 7000 genes, many of which are pivotal in biological pathways. The implications of this are profound, with consequences for evolutionary studies, population genetics, gene function and human phenotype, including elucidation of genetic susceptibility to major common diseases, the heritability of which has thus far defied full explanation. Even though this research is still in its infancy, CNVs have already been associated with a number of monogenic, syndromic and complex diseases: the development of high throughput and high resolution techniques for CNV screening is likely to bring further new insights into the contribution of copy number variation to common diseases. Amongst genes overlapped by CNVs, significant enrichments for certain gene ontology categories have been identified, including those related to immune responses and interactions with the environment. Genes in both of these categories are thought to be important in evolutionary adaptation and to be particular targets of natural selection. Thus, a full appreciation of copy number variation may be important for our understanding of human evolution.